2015
DOI: 10.1016/j.rmcr.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Dark sputum: An atypical presentation of primary pulmonary malignant melanoma

Abstract: Primary melanoma of the lung is an extremely rare clinical entity. We found only 32 cases reported in literature, and in two of these multiple brain metastases were present. We describe a case of primary lung melanoma with brain and skin metastases that presented with an initial clinical diagnosis of pneumonia.A 55-year-old white man presented with cough productive of dark sputum and fever. A chest x-ray showed a right lung infiltration. After failure to respond to usual treatment for pneumonia, bronchoscopy e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The clinical manifestations of the disease were similar to those of other thoracic malignancies, including cough, hemoptysis, dyspnea, chest pain, and signs and symptoms related to metastases. An interesting case of dark sputum was reported by Fillipini et al, which represents certainly a particular but rare clinical manifestation of PMML [20].…”
Section: Discussionmentioning
confidence: 93%
“…The clinical manifestations of the disease were similar to those of other thoracic malignancies, including cough, hemoptysis, dyspnea, chest pain, and signs and symptoms related to metastases. An interesting case of dark sputum was reported by Fillipini et al, which represents certainly a particular but rare clinical manifestation of PMML [20].…”
Section: Discussionmentioning
confidence: 93%
“…Feng et al ( 8 ) reported pulmonary MM in the form of two discrete nodules with a surrounding paving pattern in the right upper lobe and left lower lobe. Filippini et al ( 9 ) also reported primary pulmonary MM presenting as a mixed ground-glass opacity and consolidation in the right upper lobe and right lower lobe. However, the present case differs from these two previous cases in that the main radiologic finding was bilateral multiple variable-sized subsolid nodules.…”
Section: Discussionmentioning
confidence: 97%
“…Regarding the radiological features of primary pulmonary MMs, more than 80% of the cases presented with a solitary solid nodule or mass, while only < 20% presented with multiple or diffuse lesions ( 2 ). Moreover, there were only two cases of primary pulmonary MM presenting with a subsolid ground-glass opacity or consolidation ( 8 9 ). Feng et al ( 8 ) reported pulmonary MM in the form of two discrete nodules with a surrounding paving pattern in the right upper lobe and left lower lobe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung is one of the most common sites of metastasis of melanoma of extrapulmonary origin with an incidence of 70%–82% 6. A previous analysis of 130 patients with metastatic melanoma to the thorax in a single centre revealed different presentation of metastatic melanoma, for example, multiple pulmonary nodules, solitary nodule, miliary pattern, mediastinal and/or hilar adenopathy, pleural effusion, lytic bony lesions, extrapleural mass and combined lesions 7.…”
Section: Discussionmentioning
confidence: 99%